2023
DOI: 10.1111/jfb.15364
|View full text |Cite
|
Sign up to set email alerts
|

Testing assumptions underlying cabezon (Scorpaenichthys marmoratus) otolith microstructure analysis using wild‐caught juveniles and opportunistic rearing of eggs and larvae

Abstract: Otolith microstructure analysis provides critical biological and ecological information about the early life history of fishes. This information is particularly important to interpret and predict population dynamics for socio‐economically important fisheries species; nonetheless, several key assumptions underpin the use of otolith techniques. The authors validated the use of this analysis for cabezon (Scorpaenichthys marmoratus; Ayres, 1854), a long‐lived, large‐bodied cottid constituent of nearshore fisheries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Tis practical and straightforward method can be used to identify wild and reared fsh and provide a database for the study of otolith microstructure in fsh. It enriches the basic biological data of H. yarkandensis and promotes the conservation of germplasm resources of H. yarkandensis [19].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Tis practical and straightforward method can be used to identify wild and reared fsh and provide a database for the study of otolith microstructure in fsh. It enriches the basic biological data of H. yarkandensis and promotes the conservation of germplasm resources of H. yarkandensis [19].…”
Section: Discussionmentioning
confidence: 96%
“…Te researchers assessed the growth of the larval stage in detail by daily incremental analysis of otoliths [14][15][16][17]. Some studies show that otolith microstructure data can be used to reveal the impact of the environment on the growth of young fsh, the transfer process between life stages, and the performance of young survival in specifc habitats [18][19][20]. No relevant studies have been reported to discern the early life history of H. yarkandensis by otolith daily increments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation